Effects of Hydroxyethyl Starch 130/0.4 on Serum Creatinine Concentration and Development of Acute Kidney Injury in Nonazotemic Cats. (1st September 2017) - Sigrist, N.E.; Kälin, N.; Dreyfus, A.
Abstract : Background: Hydroxyethyl‐starch (HES) solutions might have renal adverse effects in humans and dogs. Objective: To determine if administration of 6% HES‐130/0.4 is associated with an increase in serum creatinine concentration and development of acute kidney injury (AKI) in nonazotemic cats. Animals: A total of 62 critically ill cats; 26 HES exposed and 36 unexposed. Methods: Retrospective cohort study (2012–2015). Serum creatinine concentrations were recorded and changes in serum creatinine concentrations before exposure (baseline) and 2–10 and 11–90 days, respectively, were determined. Development of AKI was defined as a > 150% increase or >26 μmol/L increase in serum creatinine concentration from baseline. Risk factors, such as HES administration, cumulative volume of HES (mL/kg) and number of days of HES administration leading to development of AKI, and change in serum creatinine were analyzed. Results: Cats in the HES cohort received a mean volume of 98.5 ± 76.2 mL/kg (range, 8–278 mL/kg) HES over a median of 4 (range, 1–11) days, resulting in a median dose of 20.1 (range, 8–40.5) mL/kg per day. Short‐term %change in serum creatinine concentration ( P = 0.40) and development of AKI ( P = 0.32) were not significantly different between cohorts. Multivariable logistic regression did not identify HES dose in mL/kg ( P = 0.33) and number of days of HES application ( P = 0.49) as a risk factor for development of AKI. Conclusion and Clinical Importance: Hydroxyethyl‐starch administration to critically ill nonazotemic cats seems to be safe. A larger prospective study is required to determine the effect of HES administration at higher dosages and for prolonged time periods.